(untitled) (Al-Academy, 2024)
Textiles are among the consumer products that people cannot do without, because of their utilitarian value, in addition to their aesthetic value, which expresses all aspects of society, as they are affected, like other arts, by their data Intellectual design to derive its design units from reality, and its ability to derive new design ideas resulting from the designer’s own sensitivity to the references from which design thought is derived. The research problem was determined according to the following question: What are the data of religious (Islamic) thought and its implications on the designs of modern curtain fabrics? The importance of the research was evident in shedding light on the data of religious thought and its reflections in the designs of modern curtain fabrics through the following goal: defining the data of religious (Islamic) thought and its reflections in the designs of modern fabrics.The second chapter included the theoretical framework, which consisted of two sections. The first section dealt with the concept of thought and its data, and the data of religious thought. As for the second, it included the reflection of the symbol and the significance of shapes in textile designs, and the reflection of style in modern textile designs. After that, the most important indicators that resulted from the theoretical framework were extracted, as the research procedures were determined within the third chapter by adopting the descriptive method of analysis for the purpose of analyzing the sample models from the original research population, which amounted to (16) design models (Iraqi / Turkish), which were chosen intentionally by ( 25%), as their number reached (4) design shapes distributed according to the country of origin. As for the fourth chapter, it included the results and conclusions reached by the study, the most prominent of which was: that using reality data directly in building design thought reduced the intellectual reflection of the data of Islamic art, and this was linked to the compositional organization of decorative forms and their artistic treatments.The same chapter also included recommendations, including: paying attention to studying Islamic art in the field of precise specialization (textile design) and linking Islamic thought with modern scientific theories to revive the Islamic heritage and achieve authenticity. In light of the recommendations, the research suggested conducting a comparative study between the methods of the school (Safavid and Turkish) and their implications for designs. Iraqi fabrics, as well as Arab and foreign sources